Comprehensive Evaluation of Cracking Characteristics in Sweet Potato Tubers and Screening for Crack-Tolerant Varieties - Jinxiong Liu; Fan Ding; Xue Zou; Yaoguo Qin; Shunlin Zheng; Zhitong Ren; Qiang Wang; Cuiqin Yang (Horticulturae, 2025)
This study aimed to investigate the cracking characteristics of various sweet potato germplasm resources, explore their genetic associations, and identify crack-resistant varieties. Using 40 sweet potato varieties as experimental materials, we systematically analyzed their cracking traits and assessed 24 parameters. The results indicated that genotypic differences significantly influenced sweet potato cracking (p = 1.11 × 10−16). Correlation analyses revealed that skin thickness (r = −0.81, p < 0.01), skin hardness (r = −0.50, p < 0.01), and starch content (r = −0.51, p < 0.01) were highly significantly negatively correlated with cracking incidence. Microscopic observations of the cell structure revealed that the development quality of the cork cambium and vascular cambium during the secondary growth stage plays a crucial role in maintaining the structural stability of the tuber skin, whereas the internal expansion force during the rapid growth phase is a direct factor that induces cracking. A multiple regression prediction model (R2 = 0.85) was established based on ten core indices. Furthermore, a comprehensive evaluation system for sweet potato cracking resistance was developed by integrating principal component analysis and the entropy-weighted TOPSIS model (kappa = 0.752, p = 5 × 10−6), identifying seven extremely crack-resistant and nine crack-resistant varieties. This study is the first to construct a multidimensional evaluation system for cracking traits in sweet potato, offering a reference for breeding crack-resistant varieties and developing cultivation, prevention, and management strategies.